Change in the desired number of children: A cross-country cohort analysis of levels and correlates of change - Rutstein, Shea O. (DHS Analytical Reports No. 9, 1998)
Change in a woman's desired number of children is held to be a key determinant in the demand for family planning and the decline in fertility rates. This study is based on results from Demographic and Health Surveys (DHS) and from World Fertility Surveys(WFS) and analyzes data on the amounts and the determinants of changes in fertility by tracking changes in preferences of cohorts of women and changes due to differences between cohorts. The results show that countries do not have to wait to become developed before they can reduce their rates of population growth.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The Demographic and Health Surveys (DHS) is a 13-year project to assist government and private agencies in developing countries to conduct national sample surveys on population and maternal and child health. Funded primarily by the United States Agency for International Development (USAID), DHS is administered by Macro International Inc. in Columbia, Maryland, USA.